Phytochemicals assisted green synthesis of copper oxide/cobalt oxide as efficient electrocatalyst for oxygen evolution reaction - Sarkar D.K.; Selvanathan V.; Mottakin M.; Islam M.A.; Almohamadi H.; Alharthi N.H.; Akhtaruzzaman M. (Elsevier Ltd, 2025)
Electrocatalytic water splitting is a promising solution to resolve the global energy crisis. Tuning the morphology and elemental composition is a crucial aspect in designing highly-efficient nanomaterials based electrocatalyst for water splitting. Herein, green synthesis using phytochemicals from aloe vera leaves extract was employed to hydrothermally synthesize copper oxide/cobalt oxide nanostructures on nickel foam. The reaction medium was performed in presence of mineralizers of different pH; hydrochloric acid (HCl), citric acid (CA), urea, diethyl amine (DEA) and sodium hydroxide (NaOH) to produce five different compositions of copper oxide/cobalt oxide on nickel foam. Based on FESEM and EDS analysis, it was verified that the plant mediated hydrothermal process yielded interesting morphologies and the elemental composition of the synthesized metal oxide nanostructures distinctly varied with effect to the different mineralizers used. Use of acidic mineralizers such as hydrochloric acid and citric acid favoured formation of copper oxide whereas basic mineralizers such as urea, diethyl amine and sodium hydroxide favoured formation of cobalt oxide. The green synthesis of metal oxide electrode in presence of urea exhibits the best OER electrocatalytic performance with an overpotential of 390 mV, and 453 mV for a current density of 50 mA cm?2 and 100 mA cm?2 respectively. The sample also exhibited sustained stability over 70 h, hence proving that the proposed electrode can serve as an efficient catalyst for electrocatalytic OER. ? 2023 Hydrogen Energy Publications LLC